2020
DOI: 10.5604/01.3001.0014.0503
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maternal and paternal components and breeding season on the reproductive results of New Zealand White and Californian female rabbits

Abstract: The research compares reproduction of female New Zealand White (NZW, n=55) and Californian (CAL, n=12) rabbits after mating with pure-bred Flemish Giant, Californian, and Burgundy Fawn males, as well as New Zealand White and Californian crossbred males. The influence of the dam’s breed, the birth season, and the parental component on reproduction parameters was analysed. Three groups of does were studied: those which had two litters (21 females), those which had three litters (15), and all does (irrespective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
2
1
1
Order By: Relevance
“…The result of BA and DB were similar to those reported in the literature for the same breed by Pycha et al [ 15 ], although Pollesel et al [ 16 ] have reported values higher than those found in this study. It has been reported that animals with higher birth weights have higher body weight at the first service and during their entire productive cycle [ 17 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The result of BA and DB were similar to those reported in the literature for the same breed by Pycha et al [ 15 ], although Pollesel et al [ 16 ] have reported values higher than those found in this study. It has been reported that animals with higher birth weights have higher body weight at the first service and during their entire productive cycle [ 17 ].…”
Section: Resultssupporting
confidence: 92%
“…r for traits LB, BA, LW, LWS, and SW presented a low magnitude, indicating a strong influence of environmental factors. Similar results for various litter-related traits were presented by Pycha et al [ 15 ], Behiry et al [ 30 ], and Karim et al [ 41 ]. For the WW and CW traits, the values obtained from r tend to be moderate; similar reports were presented previously [ 3 , 9 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations